Revitalising Traditional Arabic Teaching Methods through a Communicative and Contextual Approach - Maspi Fathurroziq; Adi Fadli (AR-RASYID : Jurnal Pendidikan Agama Islam, 2026)
To date, Arabic language teaching in various educational institutions still tends to adhere to a traditional approach that emphasises the structural mastery of the rules of nahwu and sharaf. In practice, this focus often results in a mechanistic learning process that leaves little room for the development of learners’ communicative skills; consequently, proficiency in Arabic frequently remains at the level of grammatical knowledge, whilst active language skills have not developed to their full potential. This study highlights the importance of revitalising Arabic language teaching methods using a qualitative research approach with library research. Data was obtained from various scientific sources relevant to the subject matter. The analysis was conducted descriptively and analytically through the interpretation of concepts and the synthesis of ideas, resulting in a comprehensive understanding. The findings of this study indicate that the revitalisation of Arabic language learning does not mean abandoning traditional methods, but rather refocusing them to make them more communicative and contextual. Grammar remains the cornerstone, but is put into practice through real-life activities such as dialogue and the analysis of texts that are closely linked to the learners’ life experiences. Teaching methods are also supported by various digital media to keep pace with the times and technological developments.